Design and Performance Investigation of Intensity Modulation/Direct Detection Scheme for C- and O-band Point-to-Multipoint Optical Networks - Saadi, Ali; Sami, Raad (Al-Nahrain Journal for Engineering Sciences, 2023)
The fifth generation (5G) and beyond mobile networks support increasing number of users with increasing bit rate per users. This has encouraged researchers to propose coherent digital subcarrier multiplexing (SCM) point-to-multipoint (P2MP) architectures to reduce the cost and complexity of optical transport networks, particularly in the metro aggregation scenario. However, coherent optical receiver is relatively costly and complexity compared with a direct-detection (DD) counterpart due to the use of a synchronized local laser. This paper addresses design issues and performance investigation of intensity modulation/direct-detection (IM/DD) P2MP optical networks. P2MP architectures are designed using digital RF multisubcarrier (MSC) waveform embedded on the intensity of continuous-wave (CW) laser beside direct-detection scheme. The design covers C- and O-band operation using a wavelength-division multiplexing (WDM) architecture. Further single- and double-polarization (SP and DP) versions are reported for each type of the networks. All the architectures are built in Optisystem version 15 environment and simulated for different network parameters, under the assumption of 25 Gbps per subcarrier data rate. The main performance measures are maximum route reach and bit rate-distance product (BDP). The simulation results indicate that DD networks can replaced the coherent counterpart when number of subcarriers per optical channel is 4. Further, the O-band P2MP networks offer high values of maximum reach and BDP than C-band counterparts.